2020
DOI: 10.3390/genes11060694
|View full text |Cite
|
Sign up to set email alerts
|

Orphan G Protein Coupled Receptors in Affective Disorders

Abstract: G protein coupled receptors (GPCRs) are the main mediators of signal transduction in the central nervous system. Therefore, it is not surprising that many GPCRs have long been investigated for their role in the development of anxiety and mood disorders, as well as in the mechanism of action of antidepressant therapies. Importantly, the endogenous ligands for a large group of GPCRs have not yet been identified and are therefore known as orphan GPCRs (oGPCRs). Nonetheless, growing evidence from animal studies, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 237 publications
(454 reference statements)
0
24
0
Order By: Relevance
“…Interestingly, while the GO terms such as G protein−coupled amine receptor activity and G protein−coupled serotonin receptor activity were specifically enriched with M1 module genes, the GO terms such as ligand-gated ion channel activity and ionotropic glutamate receptor activity were specifically enriched with M5 module genes ( Figure 3 A). These metabotropic and ionotropic receptors have been reported to be essential for various aspects of the nervous system functions [ 38 ], many of which have been associated with the pathophysiology of various psychiatric disorders [ 39 , 40 ]. Thus, our study provides mechanistic insights indicating the important role of neuronal receptor dysregulation in the pathophysiology of delirium, and the separate functional characterization of the two modules may provide information regarding the different aspects of delirium mechanisms associated with the M1 and M5 modules.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while the GO terms such as G protein−coupled amine receptor activity and G protein−coupled serotonin receptor activity were specifically enriched with M1 module genes, the GO terms such as ligand-gated ion channel activity and ionotropic glutamate receptor activity were specifically enriched with M5 module genes ( Figure 3 A). These metabotropic and ionotropic receptors have been reported to be essential for various aspects of the nervous system functions [ 38 ], many of which have been associated with the pathophysiology of various psychiatric disorders [ 39 , 40 ]. Thus, our study provides mechanistic insights indicating the important role of neuronal receptor dysregulation in the pathophysiology of delirium, and the separate functional characterization of the two modules may provide information regarding the different aspects of delirium mechanisms associated with the M1 and M5 modules.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it was reported that KYNA did not modulate the α7nAchR activities in the hippocampus of the adult mouse brain [22]. KYNA activates the orphan G-protein receptor 35 (GPR35) expressed in the glia and neurons of the hippocampus, which inhibits the adenylate cyclase and depresses excitability and synaptic transmission in the hippocampus [23]. In addition, KYNA decreased body weight without negative influence on densitometry and mandibular bone [24].…”
Section: Figurementioning
confidence: 97%
“…Several studies, including genetic loss of function studies, indicate a role for orphan GPCRs, namely ADGRB2 (BAI2) [130], GPR3 [131], GPR26 [132], GPR37 [133,134], and GPR158 [135] in the regulation of emotional behavior. The contribution of orphan GPCRs to the modulation of mood behavior has been extensively reviewed recently [136]. However, the influence of early stress on orphan GPCR expression and function, as well as the role of orphan GPCRs in mechanistically programming persistent alterations in emotionality that arise following early stress, remains poorly understood.…”
Section: Contribution Of G Protein-coupled Receptors To the Effects Omentioning
confidence: 99%